2021
DOI: 10.1037/law0000313
|View full text |Cite
|
Sign up to set email alerts
|

Using disclosure, common ground, and verification to build rapport and elicit information.

Abstract: Rapport-based approaches have become a central tenet of investigative interviewing with suspects and sources. Here we explored the utility of using rapport-building tactics (i.e., self-disclosure and interviewer feedback) to overcome barriers to cooperation in the interviewing domain. Across two experiments using the illegal behaviors paradigm (Dianiska et al., 2019), participants completed a checklist of illegal behaviors and were then interviewed about their background and interests (the interpersonal interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Prior research has suggested that rapport tactics are most likely to directly influence perceptions of rapport with the interviewer, and to indirectly influence measures of cooperation and information disclosure (see Brimbal, Dianiska, et al, 2019; Dianiska et al, 2020). A mediated model was estimated to test the indirect effect of training and the use of rapport-building tactics on cooperation and disclosure using Mplus Version 8 (Muthén & Muthén, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research has suggested that rapport tactics are most likely to directly influence perceptions of rapport with the interviewer, and to indirectly influence measures of cooperation and information disclosure (see Brimbal, Dianiska, et al, 2019; Dianiska et al, 2020). A mediated model was estimated to test the indirect effect of training and the use of rapport-building tactics on cooperation and disclosure using Mplus Version 8 (Muthén & Muthén, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Rapport is likely not the only means by which interviewers could overcome resistance and increase information yield. For example, contextual factors that are independent of an interviewer’s tactics can influence the reporting of information by interview subjects (Dawson et al, 2017; Dianiska et al, 2020). We encourage further research that examines the psychological mechanisms by which cooperation can lead to information disclosure in investigative interviews.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations